Pengaruh Kebijakan Hutang Terhadap Efisiensi Kinerja Keuangan pada PT. Indofood CBP Sukses Makmur Tbk - Mulya, Mulyati Ramadhoani; Munandar, Aris; Muthiah, Hanifah (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the effect of debt policy on financial performance efficiency at PT Indofood CBP Sukses Makmur Tbk during the period 2014–2023. Debt policy is measured by the Debt to Equity Ratio (DER), while financial performance efficiency is measured using Return On Investment (ROI). This study uses a quantitative method with an associative approach. The data used are secondary data obtained from the company's annual financial statements. The analysis techniques used include descriptive analysis, classical assumption tests (normality and autocorrelation tests), simple linear regression analysis, coefficient of determination, and hypothesis testing (t-test). The results of the study indicate that debt policy has a negative effect on financial performance efficiency, but the effect is not statistically significant (significance value 0.081> 0.05 and t count -1.999 <t table 2.306). Thus, the hypothesis stating a significant effect is rejected. This study concludes that increasing DER does not significantly affect the company's ROI, so PT Indofood CBP Sukses Makmur Tbk is advised to maintain an optimal capital structure to avoid financial risks in the future.